2021
DOI: 10.1002/jsp2.1140
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different cryopreservation media on human nucleus pulposus cells' viability and trilineage potential

Abstract: Introduction: Low back pain (LBP) is a significant cause of disability in many countries, affecting more than half a billion people worldwide. In the past, progenitor cells have been found within the nucleus pulposus (NP) of the human intervertebral disc (IVD). However, in the context of cell therapy, little is known about the effect of cryopreservation and expansion on here called "heterogenic" human NP cells (hNPCs), and whether commercially available cryopreservation media are more efficient than "commonly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…[158][159][160] Interestingly, a recent study reported that NP cells derived from trauma patients showed higher adipogenic and chondrogenic potential than those derived from degenerated IVDs. 161 Thus, we are more inclined to hypothesize that ECs, pericytes, and NPPCs are rare in the IVD, and acute trauma may induce local regeneration, which accounts for the unwanted distribution variability across donors. Due to the scarcity of desirable samples of healthy disks from young patients with vertebral fractures, this needs to be explored in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…[158][159][160] Interestingly, a recent study reported that NP cells derived from trauma patients showed higher adipogenic and chondrogenic potential than those derived from degenerated IVDs. 161 Thus, we are more inclined to hypothesize that ECs, pericytes, and NPPCs are rare in the IVD, and acute trauma may induce local regeneration, which accounts for the unwanted distribution variability across donors. Due to the scarcity of desirable samples of healthy disks from young patients with vertebral fractures, this needs to be explored in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, a need exists for novel regenerative strategies to treat intervertebral disc diseases. Currently, cell therapy [26] and growth factor injection [17] is gaining momentum, however, further validation and optimization of different regenerative products will likely be needed [64]. One potential approach for enhancing cellular products is priming the cells before transplantation [65], to promote an optimal anabolic state, such that the transplanted cells have the highest potential to contribute to the reorganization of the disc matrix or otherwise direct regional cells to do so [30].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we developed a wholetissue culture method to enable the expansion and maintenance of these Tie2-positive NPC [39]. However, several challenges remain for the adaptation of these progenitor cells as a clinical cell transplantation product, such as methods to produce large amounts of highly potent and safe cells that are ready for transplantation at the time of intervention [40]. The process of freezing and thawing cells is known to have a negative impact on their viability and potential, which may decrease the effectiveness of cell therapy [41,42].…”
Section: Introductionmentioning
confidence: 99%